Effect of Lactobacillus rhamnosus on the antioxidant activity of Cheddar cheese during ripening and under simulated gastrointestinal digestion. (September 2018) - Liu, Lu; Qu, Xiuwei; Xia, Qina; Wang, Haixia; Chen, Ping; Li, Xiaodong; Wang, Lina; Yang, Wanshuang
Abstract: This study was aimed at evaluating Lactobacillus rhamnosus for its ability to affect the antioxidant activity of Cheddar cheese during ripening and digestion. The effect of probiotic on the proteolytic patterns and antioxidant activity of Cheddar cheese during ripening was analysed. Three fractions (>10 kDa, 3–10 kDa, and <3 kDa) were separated at the end of ripening of cheese and after digestion. The results demonstrated that Lactobacillus sps dominated all stages of ripening cheese and maintained their viability at 8.44 log CFU/g at the end of ripening. The proteolysis concentrations were significantly higher in probiotic cheeses and the antioxidant activity was at its maximum at the end of ripening. Cheeses made with added Lactobacillus rhamnosus had significantly higher proteolytic activity and antioxidant activity (P < 0.05) than those without probiotics during the entire ripening time. After digestion, the number of bacteria in cheese decreased significantly ( P < 0.05 ), but the polypeptide content was increased by 37.97% and the DPPH radical scavenging ability and reducing power were increased by 7.46% and 17.58%. More small peptides were produced after digestion and the antioxidant activity of cheese correlated with proteolysis and production of small molecule polypeptides that were further enhanced upon incorporation of probiotics. The total acceptability of cheese was not affected by the addition of probiotic bacteria. Highlights: Lactobacillus rhamnosus significantly impact the counts of the Lactobacilli and Enterococci. Lactobacillus rhamnosus dominated all ripening stages of cheese and maintained high viability. Lactobacillus rhamnosus could increase the antioxidant activity of cheeses during ripening and digestion. Lactobacillus rhamnosus could promote the proteolysis and produce more small molecule polypeptide.